Current Status of Novel Biomarkers for the Diagnosis of Acute Kidney Injury: A Historical Perspective - Griffin, Benjamin R; Gist, Katja M; Faubel, Sarah (Journal of intensive care medicine, 2020)
Acute kidney injury (AKI) is a common and serious medical condition associated with significant increases in morbidity, mortality, and cost of care. Because of the high incidence and poor outcomes associated with AKI, there has been significant interest in the development of new therapies for the prevention and treatment of the disease. A lack of efficacy in drug trials led to the concern that AKI was not being diagnosed early enough for an effective intervention and that a rise in serum creatinine itself is not a sensitive-enough marker. Researchers have been searching for novel biomarkers that can not only assess a decline in kidney function but also demonstrate structural damage to the kidney and at time points earlier than increases in serum creatinine measurements allow. Over the past 10 years, there have been 3300 new publications and hundreds of new biomarkers investigated, yet concern still remains regarding AKI biomarker performance. The AKI biomarkers are yet to be widely utilized in clinical practice, leading some to question whether AKI biomarkers will ever reach their initial promise. However, we believe that biomarkers are an important part of current and future AKI research and clinical management. In this review, we compare the historical contexts of acute myocardial ischemia and AKI biomarker development to illustrate the progress that has been made within AKI biomarker research in a relatively short period of time and also to point out key differences between the disease processes that have been barriers to widespread AKI biomarker adoption. Finally, we discuss potential paths by which biomarkers can lead to appropriate AKI treatment responses that lower morbidity and mortality.